COVID-19 self-protective practices and associated factors among secondary school students in Jimma town, Jimma, Oromia, Southwest Ethiopia - Birhanu, Zewdie; Tesfaye, Genzebie; Tareke, Kasahun Girma (Frontiers in Public Health, 2022)
Background: Since there is limited evidence regarding COVID-19 self-protective practices among school students, this study assessed COVID-19 self-protective practices and associated factors among secondary school students. Methods: A school-based cross-sectional study was conducted in Jimma town, Oromia, Southwest Ethiopia, from May 25 to June 10, 2021. The total sample size was 634, and students were randomly selected from public and private secondary schools. A self-administered questionnaire was used for data collection. The data were entered into Epidata 3.1 and analyzed using SPSS 21.0 software. Descriptive statistics such as proportion and mean were computed to describe the findings. The composite index was computed for each dimension. Linear regression analysis was used to identify predictors of self-protective practice. Local polynomial smoothing graph was done using Stata 12 software to visualize the relationship between a significant variable to an outcome variable. Results: A total of 576 respondents participated in this study, which made a response rate of 90.85%. The mean score for overall knowledge was 31.40 (SD±8.65). Knowledge about COVID-19 symptoms and preventive practices had mean score of 23.93 and 45.96, respectively. The mean scores for perceived vulnerability, severity, benefits, barriers, self-efficacy and school support were 26.37, 33.21, 43.13, 16.15, 33.38 and 25.45, respectively. The mean score for self-protective practice was 28.38 (SD± 11.04). As perceived benefit (AOR= 0.199, p=0.000, 95%CI: 0.094-0.304), perceived school support (AOR= 0.125, p=0.009, 95%CI: 0.032-0.218) and self-efficacy (AOR=0.186, p=0.000, 95%CI: 0.102-0.270) increased, COVID-19 self-protective practices increases and vice versa. However, age (AOR= -0.873, p=.006, 95%CI= -1.495, -.251), perceived vulnerability (AOR= -0.107, p= .021; 95%CI= -.199- -.016) maternal educational status (no formal education) (AOR= -5.395, p=.000, 95% CI= -7.712--3.077) had negatively associated with self-protective practices. Conclusions: COVID-19 self-protective practice unsatisfactory. Perceived benefit, perceived school support and self-efficacy positively associated with it. However, student’s age, perceived vulnerability and maternal education (no formal education) were negatively associated with COVID-19 self-protective measures among secondary school students. The findings underscores that there is a need to conduct risk communications among students. Similarly, awareness creation intervention should be conducted targeting to mothers with no formal education.